Effects of temperature and humidity on cow respiration rates in three Kansas and two Nebraska freestall barns - Harner, Joseph P.; Smith, John F., 1962-; Brouk, Michael J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Temperatures and humidities outside and inside freestall barns and cow respiration rates were monitored on three Kansas and two Nebraska commercial dairy farms during the summer of 1999. All farms had 4-row freestall buildings with different cooling systems. The first Kansas barn could be cooled naturally and mechanically using evaporative cooling pads located on the east and west walls. The second Kansas barn was ventilated naturally by manually lowering the sidewall curtains and without sprinkling or ventilation systems. The third Kansas barn was ventilated naturally and equipped with fans located over the freestalls and feed-line sprinklers. The first Nebraska barn was ventilated naturally and equipped with a sprinkler system over the feed line and fans over the freestalls. The second Nebraska barn was ventilated mechanically using evaporative cooling, fans installed over the freestalls, and a sprinkler system over the feed line. Evaporative cooling did not favorably modify the barn environment. It increased or decreased humidity and offset the effect of a lower barn temperatures, resulting in greater respiration rates of cows and overall less cow comfort than other systems that provided fans or sprinklers or both.
Keywords: Dairy; Environmental stress; Heat stress; Dairy cattle